2015
DOI: 10.1016/j.arcontrol.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Fault detection and isolation for a wind turbine benchmark using a mixed Bayesian/Set-membership approach

Abstract: This paper addresses the problem of fault detection and isolation of wind turbines using a mixed Bayesian/Setmembership approach. Modeling errors are assumed to be unknown but bounded, following the set-membership approach. On the other hand, measurement noise is also assumed to be bounded, but following a statistical distribution inside the bounds. To avoid false alarms, the fault detection problem is formulated in a set-membership context. Regarding fault isolation, a new fault isolation scheme that is inspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In [76], artificial neural network was used to estimate nonlinear term in wind turbine model, and linear matrix inequality optimization was addressed to find an optimal observer gain so that a robust actuator fault estimation was achieved for 4.8 MW wind turbine Benchmark system. In [77], fault detection and isolation for wind turbines were addressed by using a mixed Bayesian/Set-membership, where modeling errors were described as unknown but bounded perturbations from the viewpoint of set membership method, while measurement noises were characterized as bounded noises following a statistical distribution. The approaches in [76,77] are actually a hybrid of model-based and datadriven approaches.…”
Section: Hybrid Fault Diagnosis For Wind Turbine Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [76], artificial neural network was used to estimate nonlinear term in wind turbine model, and linear matrix inequality optimization was addressed to find an optimal observer gain so that a robust actuator fault estimation was achieved for 4.8 MW wind turbine Benchmark system. In [77], fault detection and isolation for wind turbines were addressed by using a mixed Bayesian/Set-membership, where modeling errors were described as unknown but bounded perturbations from the viewpoint of set membership method, while measurement noises were characterized as bounded noises following a statistical distribution. The approaches in [76,77] are actually a hybrid of model-based and datadriven approaches.…”
Section: Hybrid Fault Diagnosis For Wind Turbine Systemsmentioning
confidence: 99%
“…In [77], fault detection and isolation for wind turbines were addressed by using a mixed Bayesian/Set-membership, where modeling errors were described as unknown but bounded perturbations from the viewpoint of set membership method, while measurement noises were characterized as bounded noises following a statistical distribution. The approaches in [76,77] are actually a hybrid of model-based and datadriven approaches.…”
Section: Hybrid Fault Diagnosis For Wind Turbine Systemsmentioning
confidence: 99%
“…A comprehensive literature review in Bayesian wind turbine FD can be found in . There, some other methods can be found that have been proposed more recently, such as Bayesian and non‐Bayesian based fault diagnosis approaches including non‐stationary stochastic embedding (NSSE), robust risk adjusted controllers and probabilistic fault detection Bayesian Markov chain Monte Carlo (MCMC).…”
Section: Introductionmentioning
confidence: 99%
“…Mode-matched filter: For each robust estimator, the estimated meanx j (k + 1) is calculated under the current system condition w(k) = j. According to the calculation process of a single robust estimator in Section 3.2, the gain L j (w(k)) can be given by (27); the robust estimator (REs) can be given by (20), and the robust estimator residuals r j (k + 1), weighting matrix T j (w(k + 1)), and covariance matrix S j (w(k + 1)) will be updated in a similar way.…”
Section: Stochastic Hybrid Estimation Algorithmmentioning
confidence: 99%
“…A lot of research has been started in recent years for the fault diagnosis and isolation of wind turbines [22][23][24][25][26][27][28][29]. Karim [22] designed an observer scheme for FDI, which is integrated with a maximum-shift strategy and a time-varying Kalman filter for the additive and multiplicative measurement failures of voltage and current.…”
Section: Introductionmentioning
confidence: 99%